2014
DOI: 10.1371/journal.pone.0084935
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 7 Is Associated with Symptomatic Lesions and Adverse Events in Patients with Carotid Atherosclerosis

Abstract: BackgroundAtherosclerosis is a major cause of cerebrovascular disease. Matrix metalloproteinases (MMPs) play an important role in matrix degradation within the atherosclerotic lesion leading to plaque destabilization and ischemic stroke. We hypothesized that MMP-7 could be involved in this process.MethodsPlasma levels of MMP-7 were measured in 182 consecutive patients with moderate (50–69%) or severe (≥70%) internal carotid artery stenosis, and in 23 healthy controls. The mRNA levels of MMP-7 were measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 19 publications
4
57
0
10
Order By: Relevance
“…MMP-7 has been linked to human atherosclerosis 41 and to incident cardiovascular disease, 42 but this is the first study linking MMP-7 to incident ischemic stroke.…”
Section: Matrix Metalloproteinase-7mentioning
confidence: 94%
“…MMP-7 has been linked to human atherosclerosis 41 and to incident cardiovascular disease, 42 but this is the first study linking MMP-7 to incident ischemic stroke.…”
Section: Matrix Metalloproteinase-7mentioning
confidence: 94%
“…Johnson et al [32] showed that a specific MMP-12 inhibitor could retard the development of atherosclerosis and increase fibrosis within the plaque in an atherosclerotic mouse model. Also, it was found that patients with carotid atherosclerosis had markedly increased levels of MMP-7 in plasma, especially whom with newly diagnosed symptoms [33]. Silencing MMP-9 by RNA interference in the mice arteries had been shown to increase the thickness of the fibrous cap [34].…”
Section: Let-7g and Extracellular Matrix (Ecm) Or Collagenmentioning
confidence: 99%
“…Localized production of MMP-7 by fully activated macrophages has been identified at the interface between the lipid core and fibrous cap, a divergence from the pattern of MMP-1, 3, and 9 secretion at plaque shoulders [70]. Proteolytic activity in this region may weaken apposition of the cap and predispose to plaque rupture, a scenario supported by the elevated MMP-7 plasma levels identified in patients with symptomatic carotid lesions [71]. Transcriptional activation of MMP-7 has been documented in hypoxic macrophages and the relevance of this physiologic adaptation to the regional production in atheromatous plaques remains to be determined [72]; however, a relationship to the initiation of angiogenesis ought to be considered.…”
Section: Matrilysinmentioning
confidence: 99%
“…Likewise, patients with plaques possessing elevated MMP-12 have a greater than 3-fold risk of stroke over the same timeframe [89]. Those with preoperative symptomatic carotid lesions have demonstrated elevated plasma levels of MMP-7 and associated increased all-cause mortality during an 8-year follow-up period, with this correlation being stronger than that between either age or increased CRP and mortality in this population [71]. Tracking the inflammatory biomarker CRP has repeatedly proven to be prognostic for stroke, however, and colocalization of MMP-10 with CRP in rupture-prone regions of carotid atherosclerotic plaques has led to the investigation of MMP-10 as a clinically relevant biomarker, particularly in patients with elevated CRP [67,68].…”
Section: Biomarkersmentioning
confidence: 99%